Students’ Perceptions of the Fairness in EFL Classroom Assessment - Yuniarti Yuniarti; Sunarlia Limbong; Citra Prasiska Puspita Tohamba (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
In any educational setting, assessment of teaching must support accurate and trustworthy assessment results. Fairness is one of the most important aspects of classroom assessment in addition to validity and reliability. The aim of this study is to explore the students’ perception of fairness in EFL classroom assessment. The research method was a descriptive study using a purposive sampling technique with the participation of 75 EFL students from 3 different universities; religious university, education Company-Sponsored Programs and open university. The questionnaire and interview were used to collect data on perceptions of EFL students on the fairness in classroom assessment and observation was applied to gain the data in the classroom assessment process. The result showed that the students had different perceptions of the assessment practices. Most of them were not satisfied with the assessment practices and they did not feel like it was disadvantageous to some participants and irrelevant, especially based on their socio-economic status. Moreover, the interpretation of teaching assessments should be consistent with measurement and evaluation standards without ignoring the students’ socioeconomic status. The final part of the paper can be applicable in Second Language Acquisition issues, since it explored the different sight from first language acquisition and the students’ diversity.